Pelaksanaan Supervisi Coaching oleh Kepala Sekolah dalam Peningkatan Kompetensi dan Motivasi Guru Sekolah Dasar Negeri di Kecamatan Bambel, Kabupaten Aceh Tenggara - Yusnidar, Yusnidar; Bahri, Saiful; Marisa, Riandi (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study aims to analyze the implementation of coaching supervision by school principals in enhancing teacher competence and motivation at public elementary schools in Bambel District, Aceh Tenggara Regency. Coaching supervision, which focuses on empowering teachers through collaborative guidance tailored to professional needs, was carried out through stages of planning, implementation, evaluation, and follow-up. Employing a qualitative method with a case study design, the research was conducted from July to December 2024. Data were collected through interviews, observations, and documentation. The findings indicate that coaching supervision plays a significant role in improving teachers’ pedagogical, professional, social, and personal competencies, while also exerting a positive influence on their work motivation. Challenges identified include the principals’ limited time availability and teachers’ initial lack of understanding of the coaching process. The study recommends further training for school principals and the provision of supporting facilities to optimize coaching supervision as a means of improving the quality of education.